The Future Internet Future Internet Assembly 2012: From Promises to Reality - Alvarez, Federico; Cleary, Frances; Daras, Petros; Domingue, John; Galis, Alex; Garcia, Ana; Gavras, Anastasius; Karnourskos, Stamatis; Krco, Srdjan; Li, Man-Sze; Lotz, Volkmar; Müller, Henning; et al. (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
Irrespective of whether we use economic or societal metrics, the Internet is one of the most important technical infrastructures in existence today. It will serve as a catalyst for much of our innovation and prosperity in the future. A competitive Europe will require Internet connectivity and services beyond the capabilities offered by current technologies. Future Internet research is therefore a must. The Future Internet Assembly (FIA) is a successful and unique bi-annual conference that brings together participants of over 150 projects from several distinct but interrelated areas in the EU Framework Programme 7. The 20 full papers included in this volume were selected from 40 submissions, and are preceded by a vision paper describing the FIA Roadmap. The papers have been organized into topical sections on the foundations of Future Internet, the applications of Future Internet, Smart Cities, and Future Internet infrastructures.